Macroinvertebrate communities from the shallow soft-bottoms of Deception Island (Southern Ocean): A paradise for opportunists. (June 2017) - Angulo-Preckler, Carlos; Leiva, Carlos; Avila, Conxita; Taboada, Sergi
Abstract: Deception Island (South Shetland Islands) is an atypical spot in its Antarctic context, being a still active volcano with a submerged caldera. Although the sea-floor of its enclosed bay, Port Foster, has been extensively studied from 40 m down, little is known about the macrozoobenthic composition of its shallower areas. The aim of this study was to characterize the so far unexplored soft-bottom marine macroinvertebrate communities living within the first few meters depth in Port Foster. Eight sampling stations were selected, and three replicates per station and depth (5 and 15 m) were collected by SCUBA diving using 0.008 m -2 corers. Six clusters of samples were distinguished, showing a high variability in the composition of the shallow-water macrofauna. This heterogeneity did not appear to be related to the proximity of the sites to the open sea (entrance of the caldera) or depth, nor to the sediment type or the organic matter content. Overall, the assemblages within each cluster were generally dominated by highly abundant opportunistic species, including the annelids Capitella perarmata, Mesospio moorei, Leitoscoloplos kerguelensis, Apistobranchus glacierae, and Tharyx cincinnata, the amphipod Cheirimedon femoratus, and the bivalve Aequiyoldia eightsii . The remarkably high densities reported in several stations, suggest that the shallow-water environment of Port Foster is highly productive. In light of these results, we propose a general trophic web for the shallow waters of Port Foster linking the unusually high densities of macroinvertebrates with the also high occurrence of megafaunal echinoderms present in this area.